2020
DOI: 10.3389/fonc.2020.582396
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Regulate Metabolic Phenotypes During Multicellular Tumor Spheroids Progression

Abstract: During tumor progression, cancer cells rewire their metabolism to face their bioenergetic demands. In recent years, microRNAs (miRNAs) have emerged as regulatory elements that inhibit the translation and stability of crucial mRNAs, some of them causing direct metabolic alterations in cancer. In this study, we investigated the relationship between miRNAs and their targets mRNAs that control metabolism, and how this fine-tuned regulation is diversified depending on the tumor stage. To do so, we implemented a pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…miRs have also been implicated in BC metabolic changes, through their regulation of key mRNAs involved in metabolism. A recent study by Muciño-Olmos et al identified regulatory interactions between miRs and metabolic mRNAs representative for proliferative and quiescent BC phenotypes [ 31 ]. The miR and mRNA expression patterns of three-dimensional (3D) spheroid cultures of the BC cell line MCF7 (ER+) were compared.…”
Section: Bcc Dormancy and Carbon Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…miRs have also been implicated in BC metabolic changes, through their regulation of key mRNAs involved in metabolism. A recent study by Muciño-Olmos et al identified regulatory interactions between miRs and metabolic mRNAs representative for proliferative and quiescent BC phenotypes [ 31 ]. The miR and mRNA expression patterns of three-dimensional (3D) spheroid cultures of the BC cell line MCF7 (ER+) were compared.…”
Section: Bcc Dormancy and Carbon Metabolismmentioning
confidence: 99%
“…1a ). While these miR sets caused downregulation in the quiescent BCC models, the same sets were upregulated in their proliferative BC model, further suggesting a metabolic switch in the miRNA BC landscape which directly affects glycerophospholipid, N-Glycan and glucose metabolism [ 31 ].…”
Section: Bcc Dormancy and Carbon Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, research into the metabolic properties of dormant BCCs is limited, and the studies performed to date are contradictory (35). For example, several reports have concluded that a shift in BCCs towards glycolysis is responsible for BCC dormancy, whereas others have reported that a BCC shift towards OXPHOS induces dormancy (35,(67)(68)(69)(70). Notably, none of these studies explained a metabolic mechanism for BCC recurrence.…”
Section: Msc-ev Treatment Differentially Influences Respiration In Mc...mentioning
confidence: 99%
“…This binding causes suppression of translation and mRNA degradation of the target genes [17]. MicroRNAs regulate the genes involved in important physiological processes such as metabolism, cell division, differentiation, and apoptosis [18,19]. MiR-423-5p is found on chromosome 17 [20]; it regulates insulin receptor substrates 2 and Phosphoinositide-3-Kinase Regulatory Subunit 3 PIK3R3 gene and, therefore, may be involved glucose and lipid metabolism [21].…”
Section: Introductionmentioning
confidence: 99%